Aquatrichlorido(1-cyanomethyl-4-aza-1-azoniabicyclo[2.2.2]octane-κN4)copper(II) monohydrate - Qinqin Zhou; Yi Zhang (Acta Crystallographica Section E, 2012)
The asymmetric unit of the title compound, [CuCl3(C8H14N3)(H2O)]·H2O, comprises a neutral complex and a molecule of free water. The complex contains coordinated CuII ions, with Cu—Cl distances ranging from 2.3471 (8) to 2.4011 (8) Å, and with Cu—N and Cu—O distances of 2.0775 (19) and 2.0048 (18) Å, respectively. The resulting coordination polyhedron is a trigonal bipyramid with the Cl atoms in the equatorial plane. In the crystal, O—H...Cl and O—H...O hydrogen bonds link the molecules into a three-dimensional structure.